Empowerment of PKK Women through Google Form Training in Mampang Village, Depok City - Valentine, Hany Maria; Zulkarnain, Iskandar; Fauziyah, Fauziyah; Kurnia, Mega Tri (Jurnal Pengabdian West Science, 2025)
Technological adaptation at all levels of society, one of which is the PKK organization that faces digital gaps in data management and activity administration. This Community Service activity aims to improve the digital literacy of PKK members of Mampang Village, Depok City through Google Form training. The method used was a participatory approach and practice-based learning with 15 participants who were PKK members. The activity will be held on May 10, 2025 at the Multipurpose Hall of Mampang Village through the stages of preparation, implementation, and evaluation. The results showed a significant improvement in participants' technical ability to use Google Forms for digitization of activity registration systems, community needs surveys, and organizational coordination. The program successfully drives social transformation by increasing awareness of the importance of data in decision-making, organizational transparency, and motivation for continuous learning at the community level.
Keywords: PKK empowerment; Digital Literacy; Google Form; Community Service; Digital Transformation